Environmental and Processing Contaminants from Pahs and Furan - Peace, C. E.; Osuji, L. C.; Osu, C. I. (Advances in Social Sciences Research Journal, 2022)
Maintaining an adequate, safe food supply has been a major goal of the Federal Government since 1906, when the first Federal food and drug law was signed into law. Historically, chemicals such as salt, sugar, and wood smoke have been used to preserve foods. Modern food technology relies extensively on the use of chemicals not only for preservation but also to produce appealing colors, flavors, aromas, and textures. Most developed countries now have food laws designed to permit the use of such chemicals in food under conditions judged to be safe. These chemicals are not considered adulterants or contaminants and are classed as intentional additives. Other chemicals may enter food as a result of their use in food production, handling, or processing. Such substances maybe legally permitted if they are unavoidable under good manufacturing practices and if the amounts involved are considered safe. These chemicals are classed as incidental additives. The presence of both these classes of chemicals in food is controlled by regulation.